Rescue Stories - Peckham, Lori; Nang Chan Yeema (Hagerstown, Maryland, United States Review and Herald Publishing Association, 2011)
Falling into a bear trap - on top of the bear. Being chased by a hungry crocodile. Tumbling headfirst into a barrelful of icy water. Stepping on a snake in the dark. Even in the worst situations, we can depend on God for help.
Keywords: Adult Nonfiction